PENGEMBANGAN MEDIA PEMBELAJARAN BIG BOOK BERBASIS CERITA RAKYAT PADA MATA PELAJARAN BAHASA INDONESIA KELAS I UPTD SPF SD NEGERI CIBUBUKAN ACEH SINGKIL - Risfa Vidya Hastuti; Sutarini; Rita Destini; Dara Fitrah Dwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to develop a big book learning media based on local folklore with the help of the Canva application, and to evaluate student responses and its feasibility. This big book is based on local legends, uses Indonesian, and presents relevant images to attract students' interest in learning. The research method used is Research and Development (R&D) with the ADDIE model, but only three stages are applied: Analysis, Design, and Development. At the analysis stage, pre-research was conducted at the UPTD SPF SDN Cibubukan, where interviews with grade I teachers revealed that learning Indonesian was less interesting for students. At the design stage, the researcher designed a big book using Canva, and at the development stage, the big book media was validated by material experts, media experts, and teachers. The validation results showed a feasibility score of 95% from material experts, 94% from media experts, and 95% from teachers, all of whom concluded that this media was very suitable for use in learning. The big book media developed can be applied as an initial step in the teaching and learning process, indicating that this folklore-based big book is very suitable for use in learning Indonesian.